The level of mother's knowledge about types of family planning with decision-making ability in terms of family support at the Kalibata Village Health Center 1 - Sekar, Meylita; Setiyadi, Agung; Hijriyati, Yoanita (Journal of Nursing and Midwifery Sciences, 2022)
Family planning is a husband and wife effort to measure the number and distance of children they want. The business in question includes contraception or prevention of pregnancy and family planning. The basic principle of the contraceptive method is to prevent male sperm from reaching and fertilizing a woman's egg (fertilization) or preventing a fertilized egg from implanting (attaching) and developing in the uterus. Objectives: To describe the effect of mother's level of knowledge about types of family planning on decision-making abilities in terms of family support at the Kalibata Village Health Center 1. This research method uses quantitative research with an analytical correlation design with a Cross-Sectional research design with a sample of 42 respondents. The results of this study that the level of knowledge with decision making to choose family planning obtained p = 0.003 (p < 0.050), then the hypothesis in this study is Ha is accepted and H0 is rejected. From these results, it can be concluded that there is a positive and significant relationship between the level of knowledge and the decision making to choose family planning, meaning that the higher the individual's knowledge level, the higher the decision making to choose family planning in the individual. Family Support with the decision to choose family planning obtained p value = 0.024 (p < 0.050), then the hypothesis in this study is Ha is accepted. From these results it can be concluded that there is a positive and significant relationship between family support and decision-making to choose family planning, meaning that the higher the individual's family support, the higher the decision-making to choose family planning for the individual